The Transformation of Islamic Education Management to Improve the Quality of Educational Institutions in the Digital Era - Imro'atus Sholihah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The rapid development of digital technology has encouraged Islamic educational institutions to transform their management systems to improve institutional quality and competitiveness. This study aims to analyze the transformation of Islamic education management in improving the quality of educational institutions in the digital era. This research used a qualitative approach with a library research method by analyzing scientific articles and academic references related to Islamic education management, digital transformation, leadership, and quality improvement. Data were collected through documentation techniques and analyzed using content analysis by identifying, categorizing, and synthesizing findings from previous studies. The results show that the transformation of Islamic education management involves several important aspects, including digital-based educational governance, digital leadership development, human resource competency improvement, technology-based quality management strategies, and the integration of Islamic values into digital transformation. The findings indicate that successful digital transformation requires not only technological adoption but also organizational readiness, innovative leadership, and the strengthening of Islamic values. This study implies that Islamic educational institutions need to develop adaptive management models that integrate digital innovation and Islamic principles to achieve sustainable educational quality improvement